PENGARUH STRUKTUR MODAL, LIKUIDITAS, KOMISARIS INDEPENDEN, DAN STRUKTUR ASET TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR KONSTRUKSI BANGUNAN DI BURSA EFEK INDONESIA - Salimah Salimah; Anita Wijayanti; Endang Masitoh (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of the capital structure, liquidity, independent commissioners and assets structure on financial performance. The sample in this study is a building construction sector company listed on the Indonesia Stock Exchange for the period 2013 - 2017 with a total of 36 samples. The type of research used is quantitative research. The sampling technique used was purposive sampling with certain criteria, the data analysis technique used was multiple linear regression. The results of the t test show that the variables of capital structure and independent commissioners have a significant and significant effect on financial performance, while the liquidity variable and assets structure have no significant and no significant effect on financial performance. The test results of the coefficient of determination indicate that the independent variable can affect the dependent variable by 28.2% while 71.8% is influenced by other variables.